The Release of Peripheral Immune Inflammatory Cytokines Promote an Inflammatory Cascade in PCOS Patients via Altering the Follicular Microenvironment - Liu, Yishan; Liu, Hao; Li, Zitao; Fan, Hualin; Yan, Xiumin; Liu, Xiao; Xuan, Jianyan; Feng, Du; Wei, Xiangcai (Frontiers in Immunology, 2021)
Background Hormones and immune imbalance are critical factors in polycystic ovary syndrome (PCOS). The alternation of immune microenvironment of oocytes may play a significant role in infertility of PCOS patients. Objective This study explores the role of follicular fluid microenvironment change in inflammatory pathways activation of granulosa cells (GCs) in PCOS women infertility. Methods We enrolled 27 PCOS patients and 30 controls aged 22 to 38 years who underwent IVF and collected their luteinized granulosa cells (LGCs). Meanwhile, a granulosa-like tumor cell line (KGN) as a cell-model assisted this study. Key inflammatory markers in human ovarian GCs and follicular fluid were detected by RT-qPCR, Western blotting, or ELISA. The KGN cells were treated with follicle supernatant mixed with normal medium to simulate the microenvironment of GCs in PCOS patients, and the inflammation indicators were observed. The assembly of NLRP3 inflammasomes was detected by immunofluorescence techniques. Dihydroethidium assay and EdU proliferation assay were used to detect ROS and cell proliferation by flow cytometry. Results Compared with normal controls (n = 19), IL-1β (P = 0.0005) and IL-18 (P = 0.021) in the follicular fluid of PCOS patients (n = 20) were significantly increased. The NF-κB pathway was activated, and NLRP3 inflammasome was formatted in ovarian GCs of PCOS patients. We also found that inflammation of KGN cells was activated with LPS irritation or stimulated by follicular fluid from PCOS patients. Finally, we found that intracellular inflammation process damaged mitochondrial structure and function, which induced oxidative stress, affected cellular metabolism, and impaired cell proliferation. Conclusion Inflammatory microenvironment alteration in the follicular fluid of PCOS patients leads to activated inflammatory pathway in GCs, serving as a crucial factor that causes adverse symptoms in patients. This study provides a novel mechanism in the inflammatory process of PCOS.